Implementasi Discovery Learning Berbantuan Liveworksheet Dalam Meningkatkan Keterampilan Berpikir Kritis Siswa - Nadivatul Hasanah; Try Hartiningsih; Eva Ari Wahyuni; Aditya Rakhmawan; Dwi Bagus Rendy Astid Putera (Journal of Progressive Science Education, 2025)
The purpose of this study was to determine the improvement of students' critical thinking skills after implementing the discovery learning model assisted by liveworksheets. This study used quantitative research with a quasi-experimental method with a non-equivalent group design. The study was conducted at the UPTD of SMPN 4 Bangkalan. The study population was all seventh grade students of the 2024/2025 academic year. Sampling used a purposive sampling technique. The sample used was class VII-H. The data analysis technique used the n-gain test. The results showed that there was an increase in students' critical thinking skills after implementing the discovery learning model assisted by liveworksheets in the moderate category, with an average n-gain score of 0.66.